Big Nate. Aloha! - Peirce, Lincoln ([Kansas City, Missouri] : Andrews McMeel Publishing, 2021)
Aloha can mean hello or goodbye--which makes it the perfect word for sixth grader Nate Wright. Why? Because Nate doesn't know whether he's coming or going. Will his romance with Daisy sizzle or fizzle? Will his hair survive Teddy's cut-rate barber skills? And when Nate spots a crime in progress at Klassic Komix, can he find his inner superhero?
These strips appeared in newspapers from February 26, 2017, through September 2, 2017.
2.8.
3-6.
GN340L
Keywords: Big Nate -- Comic books, strips, etc. -- Juvenile fiction; Friendship -- Comic books, strips, etc; Middle school -- Comic books, strips, etc; Conduct of life -- Comic books, strips, etc; Comics (Graphic works); Graphic novels; Humorous comics; Friendship -- Fiction; Middle schools -- Fiction; Conduct of life -- Fiction